2014
DOI: 10.1111/acer.12404
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Intake During Adolescence, but not Adulthood, Promotes Persistent Deficits in Risk-Based Decision Making

Abstract: Background Adolescent alcohol use is a major public health concern and is strongly correlated with the development of alcohol abuse problems in adulthood. Adolescence is characterized by maturation and remodeling of brain regions implicated in decision making and therefore may be uniquely vulnerable to environmental insults such as alcohol exposure. We have previously demonstrated that voluntary alcohol consumption in adolescence results in maladaptive risk-based decision making in adulthood. However, it is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 53 publications
11
60
4
Order By: Relevance
“…Importantly, a previous study in which rats were pair-housed and exposed to intragastric alcohol or control administration during adolescence observed that alcohol-treated animals showed increased lever-pressing behavior during Pavlovian conditioning consistent with the results outlined here (McClory and Spear, 2014), indicating that the effects of alcohol on learning are consistent across housing conditions. Finally, our work demonstrating that adolescent alcohol promotes maladaptive decision making (Nasrallah et al, 2011;Schindler et al, 2014), findings that we have previously linked to learning effects similar to the ones found here (Clark et al, 2012), have been replicated in animals that were group housed during intragastric alcohol administration in adolescence (Boutros et al, 2014). Thus the observed increase in sign-tracking behavior reported here is most likely the result of alcohol exposure rather than housing conditions.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Importantly, a previous study in which rats were pair-housed and exposed to intragastric alcohol or control administration during adolescence observed that alcohol-treated animals showed increased lever-pressing behavior during Pavlovian conditioning consistent with the results outlined here (McClory and Spear, 2014), indicating that the effects of alcohol on learning are consistent across housing conditions. Finally, our work demonstrating that adolescent alcohol promotes maladaptive decision making (Nasrallah et al, 2011;Schindler et al, 2014), findings that we have previously linked to learning effects similar to the ones found here (Clark et al, 2012), have been replicated in animals that were group housed during intragastric alcohol administration in adolescence (Boutros et al, 2014). Thus the observed increase in sign-tracking behavior reported here is most likely the result of alcohol exposure rather than housing conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Daily adolescent alcohol intake was stable across the 20-day exposure period (F (19,266) day = 1.62, NS) and averaged 11.5 ± 0.98 g/kg, comparable to our previous studies ( Figure 1b; Nasrallah et al, 2011;Schindler et al, 2014). The caloric intake was comparable for alcohol-and controlexposed animals (F (6,172) day × group = 1.69, NS; F (1,29) group = 0.184, NS) and both groups increased in body weight to the same extent over the course of the 20-day exposure period (Figure 1c; F (1,35) day × group = 1.57, NS; F (1,29) group = 1.48, NS).…”
Section: Alcohol Intakesupporting
confidence: 90%
See 3 more Smart Citations